Simulation model to realize soybean self-sufficiency and food security in Indonesia: A system dynamic approach - Paryanto Edi; Harisudin Mohamad; Sutrisno Joko; Kusnandar Kusnandar (Open Agriculture)
This dynamic system simulation model was designed to describe Indonesia’s soybean availability system’s dynamic structure. Methodologically, this was the first application to combine the production subsystem, demand subsystem, and import subsystem in one dynamic system simulation model. This study provides an overview of the current and future conditions of the system. Readers will know how the next 20 years will be the state of the production level, soybean demand, imports, self-sufficiency ratio (SSR), and import dependency ratio (IDR) of soybean commodities in Indonesia. The forecast results were significant because it was concerned with the availability of soybeans in the future. If the future situation is not known, then it is impossible to know the anticipatory steps that need to be prepared early. The driving factor of the soybean production system lies in productivity and the size of the soybean crop area. The driving factor of the number of imports lies in demand shortage, while soybean demand depends on population growth. The simulation results showed that the increase in productivity and crop area will have an impact on the posture of the soybean availability structure in Indonesia. The changes that occurred were a shift in the SSR value to be higher and the IDR value to be lower. Finally, this article presents various policy simulations based on measurable and rational targets that stakeholders can use.